WAGE KERAMAT SEBAGAI TRADISI KOMUNAL SPIRITUAL JAWA - Hanifah, Muna Roidatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this study is to review the relevance of the Wage Keramat to Emile Durkheim's theory of community unity and Totemism. This specific research is important to do, because there are many different types of earth alms rituals in Indonesia with their respective characteristics. Therefore, the act of generalizing the whole tradition with Totemism theory is not appropriate. This research used qualitative methods and literature studies. Observations were made right at the celebration of the Wage Keramat in Sugihwaras Village, Ngancar District in order to obtain accurate data related to the description of the Wage Keramat. The literature study is sought in order to explore the theoretical framework used. The results of this study explain that, technically, the Wage Keramat is almost the same implementation as Earth Alms in general. The difference lies in the purpose of the Wage Keramat, which is as a communal anticipatory measure for the realization of a bad oath from the legendary figure of the local community. But it cannot be denied, a form of gratitude for all of the sustenance that the earth has provided is also a destination. The conclusion is Emile Durkheim's Sociology theory indeed found many matches in the phenomenon of the Wage Keramat, both in the sacred and profane categories, totemism, and taboo.Â Â Keywords: wage keramat; tradition; theory emile durkheim